THE WORLD DANCES - Valijonova Sugdiyona (International Journal of Economic Integration and Regional Competitiveness, 2024)
This article presents interesting facts about the emergence of world folk dances, their stages of development, types of dances popular in the XVIII-XIX centuries, including: “Tarantella”, “Farandola”, “Waltz”, “Mazurka”, “Polonez”, “Bal”, “Branl”, methods of their performance, originality and musical dimensions of dance movements, as well as some folk dances that are now forgotten.